Evaluation of Disaster and Emergency Assembly Areas in Arnavutköy (Istanbul) for Suitability in Disaster Processes - Harun Reşit Bağcı; Nur Seda Çağırır; Serdar Demir (Coğrafya Dergisi)
Disasters play an important social and psychological role in society. The recent losses caused by disasters such as earthquakes, floods, and forest fires in Turkey have kept this issue on the agenda. Disaster management processes are important to prevent disasters and reduce their damage. “Disaster and Emergency Assembly Areas” are established to gather citizens in safe areas and meet their needs during disaster processes. Correct location selection is important for the safety of these areas and the assembly of needs. This study investigates to what extent the disaster and emergency assembly areas in Arnavutköy, one of the highly populated districts of Istanbul, are suitable for use in disaster processes. The analytical hierarchy process (AHP), Remote Sensing (RS), and field studies were used to determine the suitability levels of the assembly areas and interpret them with samples. For this purpose, data were collected from fields and relevant institutions. Suitability analysis was performed using the parameters of distance to hazardous elements, settlement density, distance to main roads and health infrastructure, susceptibility to soil liquefaction, land cover, and slope. According to the findings, the 185 assembly areas in Arnavutköy were categorized into 5 suitability levels. It was determined that 32% of the assembly areas had the lowest and lowest suitability levels. It is thought that the 26 assembly areas at the lowest suitability level in the district are not suitable for use during disaster processes due to various risks, so these areas should be changed urgently. For assembly areas to fulfill their purpose, they need to be introduced and prepared in terms of materials, storage areas, infrastructure, and equipment that will be needed during a disaster.